MANAJEMEN PENGAWASAN PAJAK MINERAL BUKAN LOGAM DAN BATUAN DI KANTOR DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET DAERAH (DPPKAD) KOTA PALU - Sahdin, Sahdin (Katalogis, 2015)
The aim of this research is to ascertain the management of non-metallic mineral and rocks tax supervision at the office for management of regional revenue, finance and assets Palu. This is a qualitative research which emphasizing on the process and elucidating or social reality that is not examined or measured strictly from the aspect of quantity or frequency. Qualitative research is focused on social reality construction, reaction between the researcher and the sample, situational constraints which covering a research, and heavy character of a research. The focus of this research is to elucidate how social symptom is set up and clarified. The techniques of the data analysis are data reduction, data presentation, and data verification. The result of this research shows that the supervision of the management of non-metallic mineral and rocks tax in this case the taxation has been running properly, but deception still occurs in practice. It can be concluded that the supervision of taxation is less optimal. The supervision conducted by DPPKAD office Palu City toward the management of non-metallic mineral and rocks tax is basically sought to increase the income of Palu City especially from non-metallic mineral and rocks tax sector, so, by making the tax supervision effective, it is expected to improve the target achievement which has been established every fiscal year, even further improved so as the income from the tax management can contribute to the development and the progress of Palu City